URINARY TRACT INFECTIONS IN CHILDREN: ETIOLOGY AND PATHOGENESIS, CLINICAL MANIFESTATION, DIAGNOSTICS, MODERN APPROACHES TO THERAPY - A. M. Esayan; A. N. Nimgirova (Вопросы современной педиатрии, 2012)
The article covers the problem of urinary tract infections, which are the most common infectious diseases in children. The authors analyze etiology, pathogenesis, classification and clinical and diagnostic approaches to such patients. The modern methods of treatment are described in the article.t.